Performance of the new 2011 ACR/EULAR remission criteria with tocilizumab using the phase IIIb study TAMARA as an example and their comparison with traditional remission criteria. Issue 11 (29th August 2011) - Iking-Konert, Christof; Aringer, Martin; Wollenhaupt, Jürgen; Mosch, Thomas; Tuerk, Stefan; Feist, Eugen; Burmester, Gerd R
Abstract : Background: Remission is the established goal in rheumatoid arthritis (RA) treatment. Although originally defined by a disease activity score in 28 joints (DAS28) <2.6, more stringent criteria may imply the absence of disease activity. The 2011 ACR/EULAR remission criteria provide the newest and most stringent definition of remission. Objectives: To evaluate post hoc the remission by ACR/EULAR criteria and compare the criteria with the conventional DAS28 in TAMARA, an open-label phase IIIb tocilizumab (TCZ) trial including patients with active RA receiving inadequate disease-modifying antirheumatic drugs (DMARDs) or tumour necrosis factor α (TNFα) inhibitor treatment. Results: 286 patients were enrolled, 99.7% of patients were receiving a conventional DMARD and 41.6% had TNFα inhibitor pretreatment. Baseline mean DAS28 of 6.0 ± 1.0 fell to 2.6 ± 1.5 at week 24. DAS28 <2.6 was achieved by 47.6% at week 24. Remission rates with the new ACR/EULAR Boolean-based criteria for clinical studies were 15.0% after 12 weeks and 20.3% after 24 weeks. Of note, 13.5% of patients with previous TNFα blocker inadequate response still achieved remission according to the new ACR/EULAR criteria after 24 weeks. Clinical Disease Activity Index and Simplified Disease Activity Index remission rates were 24.1% and 25.2%, respectively. Conclusions: Under the definition of the new stringent 2011 ACR/EULAR remission criteria, patients with active RA despite DMARD treatment and even after inadequate response to TNFα inhibitors, receiving TCZ showed significant rates of remission. Similar remission rates were achieved, when clinical practice criteria, not inclusive of acute phase reactants, were used.